1992
DOI: 10.1093/nar/20.18.4897
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis by 06meG residues within codon 12 of the human Ha-ras proto-oncogene in monkey cells

Abstract: The first or/and the second guanines of the human Ha-ras codon 12 (normally GGC) were substituted by O6 meG residues and the modified sequence was subsequently introduced into an SV40-based shuttle vector able to replicate in both simian cells and bacteria. After replication in simian COS7 cells (proficient in O6-alkyl-guanine transferase), plasmid DNA was extracted and mutations were screened in E. coli DH5 alpha cells. The vast majority of the mutations induced by O6 meG were G----A transitions. The mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 30 publications
0
25
0
1
Order By: Relevance
“…Aspects of the mutagenicity and repair of these types of modified bases have been studied previously in mammalian cells using the site-specific mutagenesis approach (1)(2)(3)(4)(5)(6)(7)(8)(9). We have used this approach here to examine mutagenesis and repair of O 6 -methyl (m 6 G)-, O 6 -ethyl (e 6 G)-, and O 6 -benzylguanine (b 6 G), as well O 4 -methylthymine (m 4 T) in human cells.…”
Section: Introductionmentioning
confidence: 99%
“…Aspects of the mutagenicity and repair of these types of modified bases have been studied previously in mammalian cells using the site-specific mutagenesis approach (1)(2)(3)(4)(5)(6)(7)(8)(9). We have used this approach here to examine mutagenesis and repair of O 6 -methyl (m 6 G)-, O 6 -ethyl (e 6 G)-, and O 6 -benzylguanine (b 6 G), as well O 4 -methylthymine (m 4 T) in human cells.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the kinetic results of Georgiadis et al (9) on in vitro repair by the ada protein of 06-meG at position 12G2 of the rat oncogene. Slower repair at 12G2 was also proposed as a possible explanation for the higher mutagenesis observed in monkey COS cells using vectors containing the same synthetic sequences as employed here (11). Based on three independent observations, therefore, it appears that production of G:C -~A:T mutations at the second position of codon 12 of the rat and human Ha-ras oncogene may be favoured by slow AGT repair.…”
Section: Discussionmentioning
confidence: 60%
“…In some cases, where the same oligonucleotide was synthesised by both methods, identical results were obtained in mutagenesis experiments. Oligonucleotides 12G1/PE/M and 12G2/PE/M are the same as those employed in the previously published study using shuttle vectors in mammalian cells (11). All oligonucleotides employed in the construction of mutagenesis vectors were additionally purified and characterised as already described (11).…”
Section: Oligonucleotidesmentioning
confidence: 99%
See 1 more Smart Citation
“…N-Methyl-N-nitrosourea (MNU) is an alkylating agent, which has been shown to induce G:C to A:T transitions by forming O 6 -methylguanine adducts in prokaryotic and eukaryotic cells, probably through the mismatch pairing of O 6 -methylguanine with thymidine during DNA replication. [17][18][19] It has been reported that mutation frequencies were increased by MNU in a tissue-specific manner by using MNU-treated lacI transgenic mice and that the predominant mutations in MNU-treated mice were G:C to A:T transitions. 20,21) We herein describe MNU-induced mutations in various organs of not only adults but also fetuses of the rpsL transgenic mice.…”
mentioning
confidence: 99%